TRANSFORMASI CITY BRANDING DI JAKARTA MENUJU KOTA KOLABORASI - Aprianto, Happy; Nurhasana, Renny; Badry, Ahmad Ibrahim (JURNAL ILMIAH EDUNOMIKA, 2024)
A strong regional and global marketing strategy is needed to create a quality city identity. City branding that has been carried out with the tagline "Enjoy Jakarta" has not touched the identity of the city as a whole. A new identity is needed that can become a comprehensive city branding in all fields and is carried out in collaboration with all levels of society so that community involvement can be realized in solving various city problems. The use of information technology systems that optimize the use of technology can maximize public services that are more effective and efficient.